My hero academia [videorecording (DVD)] : two heroes - Nagasaki, Kenji; Clinkenbeard, Colleen; Horikoshi, Kohei, 1986- (FUNimation, 2019)
When villains hack into the world's leading hero item exhibition, I-Expo, and All Might becomes trapped, Deku and his friends must undertake a daring rescue operation.